Prevalensi Maloklusi pada Anak Usia 9−12 Tahun di Daerah Pesisir Kecamatan Malalayang Kota Manado - Pritartha S. Anindita; Sherly Gosal; Pegy E. B. Ginting (Universitas Sam Ratulangi, 2024)
Abstract: Malocclusion is a condition that deviates from normal occlusion. The prevalence of malocclusion in Indonesia is 80% of the total population. Age of 9-12 year-old is the second phase of mixed dentition phase which causes many problems. This study aimed to obtain the prevalence of tooth malocclusion in 9-12 years old children on the coastal area of Malalayang District, Manado. This was a descriptive study with a cross-sectional design. The population consisted of 819 children and the total sample was 269 children obtained by using proportionate stratified random sampling technique. This study was conducted by clinical examination and assessment based on Angle's classification. The results showed that the prevalence of malocclusion in children aged 9-12 years on the coastal area of Malalayang District, Manado was 100%, 217 children were categorized into class I malocclusion with a prevalence rate of 80.7%; 15 children were categorized into class II division 1 malocclusion with a prevalence rate of 5.6%, four children were categorized into class II division 2 malocclusion with a prevalence rate of 1.5%; and 33 children were categorized into class III malocclusion with a prevalence rate of 12.2%. In conclusion, the prevalence of maloclusion in children aged 9-12 years on the coastal area of Malalayang District, Manado, is 100%, and the most common type is Angle’s class I malocclusion. Keywords: children aged 9-12 years old; malocclusion; coastal area Abstrak: Maloklusi adalah suatu kondisi yang menyimpang dari oklusi normal. Prevalensi maloklusi di Indonesia mencapai 80% dari total penduduk. Usia 9-12 tahun merupakan fase kedua dari fase geligi campuran yang banyak menimbulkan masalah. Penelitian ini bertujuan untuk mengetahui prevalensi maloklusi pada anak usia 9-12 tahun di daerah pesisir Kecamatan Malalayang Kota Manado. Jenis penelitian ialah observasional deskriptif dengan desain potong lintang. Populasi penelitian berjumlah 819 anak dengan jumlah sampel sebanyak 269 anak yang diperoleh dengan teknik proportionate stratified random sampling. Penelitian ini dilakukan dengan pemeriksaan klinis dan penilaian maloklusi berdasarkan klasifikasi Angle. Hasil penelitian menunjukkan bahwa prevalensi maloklusi anak usia 9-12 tahun di daerah pesisir Kecamatan Malalayang Kota Manado sebesar 100%, maloklusi Angle kelas I dengan prevalensi 80,7% sebanyak 217 anak, maloklusi Angle kelas II divisi 1 dengan prevalensi 5,6% sebanyak 15 anak, maloklusi Angle kelas II divisi 2 dengan prevalensi 1,5% sebanyak empat anak, dan maloklusi Angle kelas III dengan prevalensi 12,2% sebanyak 33 anak. Simpulan penelitian ialah prevalensi maloklusi anak usia 9-12 tahun di daerah pesisir Kecamatan Malalayang Kota Manado sebesar 100% dan yang terbanyak ialah maloklusi Angle kelas I. Kata kunci: anak usia 9-12 tahun; maloklusi; pesisir pantai